2019
DOI: 10.1631/jzus.b19e0071
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: Catalpol ameliorates LPS-induced endometritis by inhibiting inflammation and TLR4/NF-κB signaling

Abstract: The original version of this article unfortunately contained a mistake. In p.823, Figs. 8c and 8d were incorrect, and the obvious pathological changes were mistakenly placed in the picture. The correct versions should be as follows:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…and produces various cytokines to participate in the inflammatory response. 3 Our results showed that PU could inhibit the expression of p‐p65 and p‐IκBα protein, which are related to inflammation. In summary, PU may inhibit the occurrence of inflammation through the NF‐κB signalling pathway.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…and produces various cytokines to participate in the inflammatory response. 3 Our results showed that PU could inhibit the expression of p‐p65 and p‐IκBα protein, which are related to inflammation. In summary, PU may inhibit the occurrence of inflammation through the NF‐κB signalling pathway.…”
Section: Discussionmentioning
confidence: 55%
“…NF‐κB induces the expression of various genes through the activation of stimulating factors such as viruses, tumour necrosis factor, B‐cell activation factor, lymphotoxins, etc. and produces various cytokines to participate in the inflammatory response 3 . Our results showed that PU could inhibit the expression of p‐p65 and p‐IκBα protein, which are related to inflammation.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations